Capsid protein identification and analysis of mature Triatoma virus (TrV) virions and naturally occurring empty particles - Agirre, Jon (2011)
Triatoma virus (TrV) is a non-enveloped +ssRNA virus belonging to the insect virus family Dicistroviridae. Mass spectrometry (MS) and gel electrophoresis were used to detect the previously elusive capsid protein VP4. Its cleavage sites were established by sequencing the N-terminus of the protein precursor and MS, and its stoichiometry with respect to the other major capsid proteins (VP1–3) was found to be 1:1. We also characterized the polypeptides comprising the naturally occurring non-infectious empty capsids, i.e., RNAfree TrV particles. The empty particles were composed of VP0–VP3 plus at least seven additional polypeptides, which were identified as products of the capsid precursor polyprotein. We conclude that VP4 protein appears as a product of RNA encapsidation, and that defective processing of capsid proteins precludes genome encapsidation.